Nitrogen fertilizer application rates and ratios promote the biochemical and physiological attributes of winter wheat - Kubar, Muhammad Saleem; Wang, Chao; Noor, Rana Shahzad; Feng, Meichen; Yang, Wude; Kubar, Kashif Ali; Soomro, Khalilullah; Yang, Chen; Sun, Hui; Hasan, Mohamed E.; Mosa, Walid F. A. (Frontiers in Plant Science, 2022)
Improper optimization of the rates and ratios of the nitrogen application can reduce grain yields and increase the nitrogen loss, thereby affect environmental quality. In addition, scarcer evidence exits about the integrative approach of nitrogen, which could effects on biochemical and physiological characteristics of wheat. Treatments were arranged as nitrogen (N) rates (00, 75, 150, 225 and 300 kg ha-1) in main plots and different nitrogen ratios were organized in subplots as 5:5:0:0 and 6:4:0:0 quantity applied at sowing, at jointing, flowering and grain filling stage. Results revealed that 225 kg N ha-1 signiﬁcantly enhanced the stomatal conductance (Gs), photosynthetic rate (Pn), intercellular CO2 (Ci), transpiration rate (Tr), and total chlorophyll by 28.5%, 42.3%, 10.0%, 15.2%, and 50% receptively at jointing stage in comparison to control (0 kg N ha-1). Nitrogen application of 225 kg N ha-1 increased the Soil Plant Analysis Development (SPAD) value, Chlorophyll a, chlorophyll b and carotenoids contents of winter wheat under 6:4:00 ratio. The trend of photosynthetic characteristics was observed greater under 6:4:00 fertilization ration as compared to 5:5:0:0. Photosynthetic rate was significantly associated with biochemical and physiological characteristics of winter wheat. In conclusion, the nitrogen dose of 225 kgha-1 and the proportion of 6:4:0:0 (quantity applied at sowing, at jointing, flowering and grain filling stage) effectively promoted the photosynthetic and other physiological characteristics of winter wheat.